Cadmium in Water Samples determined by Atomic Absorption Spectrometry after Solid Phase Extraction using DOWEX 50WX2 resin - Yuniar Yuniar; Siti Nuraini (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Pre concentration of Cd(II) in water samples was carried out by using column solid phase extraction DOWEX 50WX2 prior to flame atomic absorption spectrometry analized. The optimum extraction conditions such as pH (5), sample flow rate (1 mL min−1), volume of eluent HNO3 1N (10 mL) and sample volume (50 mL) was determined. The limit of detections was found 0.2697 µg L−1. The accuracy was determined by analyzid spiked water samples used Cd CRM 0.1 mg L-1 traceable to SRM standard solution NIST. Percent recovery and relative standard deviation were found 93% and 6%, respectively. Conclusion this preparation method effective for determination of ion Cd (II) in water with flame-SSA..Keywords: SPE,Cd, Dowex 50WX2, Flame-SSA